FINDING GRAMMATICAL ERRORS IN THE DESCRIPTIVE TEXT WRITTEN BY THE EIGHTH GRADERS OF SMP MARKUS MEDAN - Marlina Surya Indriani; Ance Rosario Siallagan; Lasmaida Nainggolan; Sondang Manik; Lastri Wahyuni Manurung (Universitas Pahlawan Tuanku Tambusai, 2023)
Abstract This research entitled